2018
DOI: 10.1037/gpr0000168
|View full text |Cite
|
Sign up to set email alerts
|

Extending B. F. Skinner's Selection by Consequences to Personality Change, Implicit Theories of Intelligence, Skill Learning, and Language

Abstract: In a rooftop office, above a Minneapolis flour mill in 1943, B. F. Skinner discovered “shaping” by training a pigeon to send a small wooden ball down a miniature alley to hit a set of toy pins. Skinner recalled that the day was one of great illumination and emboldened his later suggestions that human behaviors may arise from behavior–environment interactions that are relatively malleable (selectionism) rather than arising from hypothetical inner constructs that are relatively fixed (essentialism). The present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
(69 reference statements)
0
4
0
3
Order By: Relevance
“…Previous tests of implicit theories of personality categorized implicit theories of personality within the same dimensionality [29,30]. For example, the personality will be classified into stable/malleable traits based on the score, making the hidden implicit personality express out unconsciously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous tests of implicit theories of personality categorized implicit theories of personality within the same dimensionality [29,30]. For example, the personality will be classified into stable/malleable traits based on the score, making the hidden implicit personality express out unconsciously.…”
Section: Discussionmentioning
confidence: 99%
“…The participants were asked to describe the different life style, to read stories and then be evaluated the characters in the story so their own personal construct can be projected in the story of the characters. We can distinguish entity and incremental theorists by this process [29]. The clinical study showed Fairy Tale Test (FTT) which is compiled by Coulacoglou (1992) on fairy tale proved that fairy tales can be a projection tool for personality assessment [30].…”
Section: Literature Review and Methodsmentioning
confidence: 99%
“…Faktor bawaan cenderung bersifat menetap, stabil, sulit berubah, sedangkan faktor lingkungan (sosial) dinamis, mudah berubah dan situasional (Goddard, 2018). Beberapa ahli mengambil jalan tengah, yaitu proses terbentuknya perilaku karena interaksi personal dengan lingkungan.…”
Section: Apa Itu Amanah?unclassified
“…Este principio supone, por un lado, la introducción de la causalidad final frente a la mecánica E-R (Pérez-Álvarez, 2009) y, por otro, la alternativa al esencialismo consistente en ver los fenómenos psicológicos como si reflejaran cualidades naturales universales ya dadas (Goddard, 2018;Palmer y Danahoe, 1992). 4.…”
Section: Mayor Descubrimientounclassified